Primary Closure of a Subtotal Sternal Cleft in a 7-Day-Old Neonate - Sekelyk, R.; Kozhokar, D.; Yusifli, I.; Tammo, R.; Yemets, I. (Ukrainian Journal of Cardiovascular Surgery, 2021)
Sternal cleft is a rare congenital abnormality that results from incomplete fusion of the two lateral mesodermal sternal bars. It is generally accepted that primary repair in the neonatal period is the best treatment option. However, significant distance between the sternal bars can be challenging because of cardiac compression. The aim. We report a case of a 7-day-old neonate with a subtotal sternal cleft successfully managed by direct closure. Material and methods. A full-term male neonate weighing 3 kg was referred to our clinic for evaluation of a chest wall defect. The chest X-ray and computed tomography were performed to evaluate the malformation. Results. Surgery was performed at the age of 7 days. Postoperative period was uneventful. The patient was discharged on the postoperative day 21. The first postoperative checkup after 3 months showed satisfactory cosmetic results and normal respiratory movements. Conclusion. Despite the significant diastasis between sternal bars, primary direct closure of the sternal cleft can be safely performed in neonates.